Perceptual Validation of Nonlinear Postural Predictors of Visually Induced Motion Sickness - Teaford, Max A.; Cook, Henry E.; Hassebrock, Justin A.; Thomas, Robin D.; Smart, L. James (Frontiers in Psychology, 2020)
Virtual Reality (VR) technology has become increasingly prevalent in our society and has been used for a myriad of applications ranging from psychotherapy to training members of the military. However, one issue that arises from the use of VR is motion sickness, thus making predictors and indicators of motion sickness desirable. To date a number of indicators of motion sickness have been derived based on nonlinear characteristics of human motion recorded using motion capture systems. While it is known that nonlinear measures can be used to predict motion sickness, it is not known whether people are perceptually sensitive to these particular nonlinear parameters. The aims of this study included establishing whether individuals consistently sort phase plots of sick and well individuals’ postural motion without being explicitly being told to do so; determine what non-linear movement parameters could be used to represent these judgments; and to assess the stability of non-linear measures found to be successful at predicting motion sickness by Smart and colleagues (2014). Through two methods of analysis (perceptual and quantitative), this research demonstrated that participants can indeed sort the graphic depictions of sick and well participants’ postural motion and seem to be perceptually sensitive to nonlinear parameters (Normalized Path Length, Path Length, Elliptical Area) that are known to be predictive of motion sickness.